2018
DOI: 10.1016/j.omtm.2018.10.012
|View full text |Cite
|
Sign up to set email alerts
|

AAV8 Gene Therapy for Crigler-Najjar Syndrome in Macaques Elicited Transgene T Cell Responses That Are Resident to the Liver

Abstract: Systemic delivery of adeno-associated viral (AAV) vectors has been evaluated for the treatment of several liver diseases, including homozygous familial hypercholesterolemia, ornithine transcarbamylase deficiency, and hemophilia. Here, we evaluated this approach for the treatment of Crigler-Najjar syndrome. We administered wild-type rhesus macaques with 1.0 × 1013 or 2.5 × 1013 genome copies/kg of an AAV serotype 8 vector expressing a codon-optimized version of human uridine diphosphate glucuronosyl transferase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 38 publications
(49 reference statements)
0
8
0
Order By: Relevance
“…The potential development of an immune response against the transgene is dependent on several variables, including the tissue targeted with gene transfer, the host genetic background, and the extent of the residual expression of the donated gene. Gene transfer in a context of missense mutations and residual endogenous expression of the full length protein is unlikely to induce anti-transgene immune responses, although some preclinical studies suggest that even single amino acid variations can be recognized by the host immune system (84). Conversely, gene transfer in the context of stop mutations with no residual protein expression, is potentially more likely to result in antitransgene immunity due to the absence of central tolerance against the transgene product itself.…”
Section: Immune Responses Against the Transgene Productmentioning
confidence: 99%
“…The potential development of an immune response against the transgene is dependent on several variables, including the tissue targeted with gene transfer, the host genetic background, and the extent of the residual expression of the donated gene. Gene transfer in a context of missense mutations and residual endogenous expression of the full length protein is unlikely to induce anti-transgene immune responses, although some preclinical studies suggest that even single amino acid variations can be recognized by the host immune system (84). Conversely, gene transfer in the context of stop mutations with no residual protein expression, is potentially more likely to result in antitransgene immunity due to the absence of central tolerance against the transgene product itself.…”
Section: Immune Responses Against the Transgene Productmentioning
confidence: 99%
“…The goal of our studies was to define the mechanisms that limit efficient and durable transgene expression following liver gene therapy with AAV vectors. Previous studies with complete preclinical and clinical datasets suggest that nonhuman primates (NHPs) are better suited for evaluating key aspects of vector performance than other animal models [1][2][3][4] . We conducted initial studies in rhesus macaques using macaque-derived β-choriogonadotropic hormone (rh-β-CG) as the transgene.…”
Section: Main Textmentioning
confidence: 99%
“…53,54,138 A recent study evaluating a clinical AAV8 vector expressing human UGUT1A1 in NHPs reported a mainly transgene product T cell response and found that peripheral transgene product T cell responses did not always correlate with the local T cell response in the liver. 139 Insulin gene therapy with an AAV8 vector in nonobese diabetic (NOD) mice found that immune suppression was needed to maintain insulin expression, suggesting that liver tolerance alone was not sufficient to overcome established autoimmunity. 140 However, it should be noted that NOD mice have a genetic predisposition for autoimmunity and that the target level of insulin required for therapeutic benefit may be below the threshold need for tolerance induction.…”
Section: Liver Gene Delivery Transgene Product Immunity and Tolerancementioning
confidence: 99%